Regional, spatial and environmental indicators for an assessment of regional development, structure and potentials - Kušar, Simon (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
The article brings theoretical, methodological and practical aspects of adopting regional, spatial and environmental data, indicators and criteria for the assessment of regional structure, potentials and development within the context of regional and spatial planning. The proposal of the system of indicators is presented on the basis of the CONSPACE project.
Keywords: regionalno planiranje; regionalni razvoj; regionalna politika; prostorsko planiranje; spatial planning